Dysfunction of adaptive immunity is related to severity of COVID-19: a retrospective study. (July 2020) - Xie, Liang; Wu, Qinhan; Lin, Qunying; Liu, Xuhui; Lin, Weihua; Hao, Shengyu; Hu, Weiping; Xiang, Guiling; Lu, Hongzhou; Li, Shanqun
Background: In December of 2019, coronavirus disease 2019 (Covid-19) was reported in Wuhan, China, and has now rapidly swept around the world. Much research has been carried out since the outbreak, but few studies have focused on the dysfunction of the adaptive immunity. Methods: In this retrospective and multi-center study, 373 patients with laboratory-confirmed COVID-19 from Shanghai Public Health Clinical Center and Affiliated Hospital of Putian University were recruited. Demographic, clinical, radiological features, and laboratory data were recorded and analyzed at admission and at discharge. Results of immunological tests were followed up until the patients were discharged. Results: Of the 373 patients with COVID-19 pneumonia, 322 were in the non-severe group and 51 were in the severe group. Number of T cells, CD4+ and CD8+ T cells, and total lymphocytes declined remarkably upon admission and elevated when the patients were discharged. At admission, counts of total lymphocytes, T cells, CD4+ and CD8+ T cells, and levels of C3 and C4 in the severe group were lower than those in the non-severe group, whereas the neutrophil to lymphocyte ratio (NLR) was higher in the severe group. Counts of T cells, CD4+ and CD8+ T cells, and total lymphocytes were negatively correlated with lactate dehydrogenase and C-reactive protein. Conclusion: COVID-19 might target adaptive immunity and cause a decrease in lymphocytes, especially T cells and subsets. Physicians should pay close attention to the adaptive immunity of patients upon admission. Monitoring NLR, T lymphocytes, and subsets would help physicians with the proper diagnosis and treatment of COVID-19. The reviews of this paper are available via the supplemental material section.